The Relation How To Learn With The Learning Outcomes Indonesian Cake Of Tata Boga - Puput Nova; Elida Elida (Universitas Negeri Padang, 2021)
One of the factors that influence student learning outcomes is the way students learn. This study aims to describe the relationship between learning methods and student learning outcomes in the subject of Indonesian Cake and Cake Products at SMK Negeri 1 Padang Panjang. The method used in this research is quantitative methods which are classified into correlational research types. The population in this study was the students of class XI Food Management at SMK Negeri 1 Padang Panjang. The sample technique used was total sampling. Student learning data were obtained from distributing questionnaires which were arranged using a Likert scale model. While learning outcomes are obtained from the final report card grades. The data analysis technique used in this research is Product Moment Correlation. Based on the results of the research conducted, it was shown that the students' learning method in the subject of Indonesian cake and cake products, the Culinary Skills Competency of SMK Negeri 1 Padang Panjang was in the good category with a percentage of 76% and learning outcomes were”in the good category with a percentage of”52% with a correlation coefficient of 0.406 significance 0.02 <”0.05”or” t count> t table”(2.307> 1.699) shows that the hypothesis (Ha) is accepted, namely that”there is a positive and significant relationship between learning”methods and learning”outcomes in Indonesian Cake and Cake Products Subjects Competency of Culinary Skills at SMK Negeri 1 Padang Panjang.